Monitoring of Rivaroxaban Therapy in Hypercoagulable Dogs - Erin M. Phillips; Shauna L. Blois; Anthony C. G. Abrams‐Ogg; R. Darren Wood; Gabrielle Monteith; Benoît Cuq (Journal of Veterinary Internal Medicine)
ABSTRACT Background Measurement of rivaroxaban efficacy using the rivaroxaban‐specific anti‐Xa assay (raXa) can be used for monitoring in veterinary medicine. Detection of rivaroxaban efficacy using other hemostatic tests would make monitoring timelier and more accessible. Objectives Compare results of raXa with prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen concentration, tissue factor (TF) and kaolin‐activated thromboelastography (TEG), and thrombin generation (TG) in hypercoagulable dogs. Animals Twelve client‐owned dogs, diagnosed with hypercoagulability or thromboembolic disease, and prescribed rivaroxaban, were recruited from a tertiary referral hospital from 2020 to 2022. Methods Prospective clinical trial. Jugular vein blood samples were collected before treatment, and 1 week and 1–3 months after initiation of rivaroxaban therapy. Hemostatic tests were performed at each visit (3 h after rivaroxaban dosing). TG curve parameters lag time, endogenous thrombin potential (ETP), peak, and time to peak (ttpeak) were assessed. Results There was a significant linear relationship between raXa and PT (r2 = 0.74, p < 0.001), ETP (r2 = 0.83, p < 0.001), lag time (r2 = 0.87, p < 0.001), peak (r2 = 0.86, p < 0.001), and ttpeak (r2 = 0.86, p < 0.001). There was a weak linear relationship between raXa and kaolin‐activated TEG parameter reaction time (R) (r2 = 0.49, p = 0.026). There was no significant relationship between raXa and aPTT, fibrinogen concentration and the remainder of the TEG variables (p > 0.05). Conclusion and Clinical Importance PT and TG correlated with raXa. PT performed at a reference laboratory appeared to be a convenient method to monitor a small cohort of dogs receiving rivaroxaban therapy.